Electrorepulsion in Nanofluids: Experimental Characterization for a Stable Behavior - Vasco-Calle, D (American Society of Mechanical Engineers, 2019)
The present work in nanofluids is focusing into using the electro-kinetic phenomenal occurring around nanoparticles immersed in a base fluid as a method to stabilize a nanofluid and enhance its thermal conductivity. The electro-kinetic physic establishes, that when an electrolyte solution is in contact with a solid, an electric double layer (EDL) is produced on the solid surface. Due to the high concentration of ions with the same charge around of the particle surface, “it is possible to stabilize a nanofluid by the action of an electro repulsive force caused by ions over the nanoparticle surface and enhance its thermal conductivity as the concentration of the solutions increases”. The nanofluid samples were prepared by the two-step method and a continuous ultrasonication. 1wt% and 3wt% concentration (mass fraction) of Titanium oxide, Anatase (TiO2) nanoparticles, is added in an electrolyte solution (base fluid) made of different concentration of Potassium Chloride (KCl), and deionized water. The pH of the base fluid is maintained constant adding HEPES as a buffering agent. To measure the different level of stability for the nanofluid we used the thermal conductivity enhancement of the base fluid by nanoparticles. The experimental results under controlled temperature condition show that an electrolyte solution with nanoparticles after 20 days of preparation, presents a higher thermal conductivity with respect to the base fluid with an improvement rate ranging from 0.43±0.12% to 0.72±0.12% for 1wt%, and 2.15±0.17% to 3.03±0.21% for 3wt% of nanoparticles added respectively. The higher improvement shows sign of a major level of homogeneity of the nanofluid, and this behavior seems to be directly proportional to the KCl concentration. Copyright © 2019 ASME